Pengembangan TARM sebagai Website Pembelajaran Matematika dengan Menggunakan Flipped-classroom Learning - Maulana, Ahmad Rizqi; Manoy, Janet Trineke (MATHEdunesa, 2025)
Based on Bappenas's goal to enhance human resource competitiveness, teachers are expected to train students in technology mastery, work ethics, attitudes, innovation, and creativity. To address this challenge, accessible technology and new strategies are needed to allow teachers more time to develop students' competencies. This research aims to develop the TARM website using the flipped-classroom learning concept, evaluated based on validity, practicality, and effectiveness criteria. The development process follows the ADDIE model. Based on the analysis results, the curriculum used is the "Merdeka Curriculum", and students struggle to focus during lecture-based methods but are active during assignments.. All students have gadgets and internet access. On this research, the TARM website was tested to support learning materials on Arc Length, Sector Area, Segment Area, Central Angle, and Inscribed Angle. TARM is developed using the Laravel framework, based on the storyboard and flowchart created. Validation results showed the website was rated highly valid by media experts with a score of 3.27 and valid by subject matter experts with a score of 2.89. The trial process involved 31 students from XI grade of Senior High School, including pre-tests, summarizing learning materials from videos outside the classroom, Q&A sessions, quizzes, exercises, post-tests, and student response surveys. The results show that the TARM website is considered practical, with a mode percentage of "Yes" responses reaching 100% across all indicators and a student survey score of 87%. The website is deemed effective with an average N-Gain score of 0.7 in the medium category. Based on the research results, the TARM website can be used in mathematics learning espescially on highschool student.